Design and rationale for the Japanese Registry of Rivaroxaban Effectiveness & Safety for the Prevention of Recurrence in Patients with Deep Vein Thrombosis and Pulmonary Embolism (J'xactly) study. Issue 6 (22nd June 2018) - Okumura, Yasuo; Fukuda, Ikuo; Nakamura, Mashio; Yamada, Norikazu; Takayama, Morimasa; Maeda, Hideaki; Yamashita, Takeshi; Ikeda, Takanori; Mo, Makoto; Yamazaki, Tsutomu; Hirayama, Atsushi
Abstract : Introduction: Rivaroxaban, a factor Xa inhibitor used as a direct oral anticoagulant, is beneficial over warfarin in terms of food–drug interactions and the need for therapeutic monitoring in patients with acute venous thromboembolism (VTE), including deep vein thrombosis and pulmonary embolism. Because there is little data regarding VTE treatment in Japan, a real-world survey of Japanese patients being treated with rivaroxaban for VTE is needed. Methods and analysis: The Japanese Registry of Rivaroxaban Effectiveness & Safety for the Prevention of Recurrence in Patients with Deep Vein Thrombosis and Pulmonary Embolism has been established to investigate the clinical outcomes of rivaroxaban for the initial treatment and prevention of symptomatic recurrent VTE in Japanese patients with acute symptomatic/asymptomatic VTE. 150 institutions in Japan will enrol patients in the study; the target enrolment is 1000. All patients will be followed up two times a year for at least 18 months and up to 3 years after their enrolment. The primary outcome is symptomatic recurrent VTE occurring during the study period. The principal safety outcome is clinically relevant bleeding (ie, major bleeding or clinically relevant non-major bleeding) occurring during treatment. A clinical events committee will adjudicate all outcomes. Ethics and dissemination: The study protocol has been approved by the Nihon University Itabashi Hospital, Clinical Research Ethics Committee and all local institutional ethics committees of the participating hospitals. Findings of the study will be presented in scientific sessions and will be published in peer-reviewed journals. Trial registration number: NCT03091621, UMIN000025072; Pre-results.